The Human Resources Development Affecting the Working Efficiency of the Manufacturing Industrial Sector in the Eastern Region to Support the AEC - Pichetsiraprapa, Pipat; Thongrawd, Chairit; Somthong, Narintorn; Philajan, Wattana (Ph.D. in Social Sciences Journal, 2021)
This article research has the following objectives: (1) To study personal factors affecting the working efficiency of the manufacturing industrial sector in the Eastern Region to support the AEC; and (2) To study the human resources development affecting the working efficiency of the manufacturing industrial sector in the Eastern Region to support the AEC. The quantitative research found that: (1) The personal factors affecting the working efficiency revealed that different genders affected the working efficiency differently in both the working morale and the organizational royalty. On the other hand, there was no difference when age, education, working department, monthly earning, working duration, and quality of living in the work place were compared; and (2) The human resources development affecting the working efficiency revealed that the human resources development was at a high level. The working efficiency was at a high level. While the general relationship of the human resources management and the working efficiency was related at a statistical significant level of 0.01 The qualitative research revealed that the organization had to prepare the yearly human resources development plan and financial budgeting plan to enroll personnel who all needed internal improvement within the organization. On the other hand, the working efficiency needed success indicators for the evaluation of the goals set by the organization.